2015
DOI: 10.1088/0957-4484/27/6/065701
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of 2D sheet-like BiOCl/carbon quantum dot hybrids via a template-free coprecipitation method and their tunable visible-light photocatalytic activities derived from different size distributions of carbon quantum dots

Abstract: A series of two-dimensional (2D) interlaced BiOCl/carbon quantum dot composites (denoted as BiOCl/CQD composites) were synthesized by a template-free coprecipitation method at room temperature, and the influence of different particle size distributions of the CQDs on the physiochemical properties and photocatalytic activities of the BiOCl/CQD composites was studied. CQDs can change the morphology and increase the specific surface area of the BiOCl/CQD composites. Moreover, the particle size distribution of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…By harvesting solar energy as the source of renewable energy, photocatalysis will make significant impacts in the areas of (1) light-driven water splitting to hydrogen (H2) and oxygen (O2) (Chen et al, 2010;Bai et al, 2016;Wei et al, 2016;Putri et al, 2017;Yubin et al, 2017), (2) conversion of carbon dioxide (CO2) to energy bearing fuels (Ong et al, , 2014cTan et al, 2014Tan et al, , 2016Tan et al, , 2017Gui et al, 2015;Guo et al, 2016a;Zhang et al, 2016c), (3) mineralization of waste and pollutants (Ong et al, 2014d,e;Fang et al, 2016;Liu et al, 2016c;Topcu et al, 2016;Zhao et al, 2016b), (4) selective organic transformations (Liu et al, 2014;Zhao et al, 2016a), and (5) disinfection of bacteria (Keane et al, 2014;Bing et al, 2015) (Figure 1). Very recently, two-dimensional (2D) semiconductor photocatalysts have triggered a renaissance of interest in the field of energy, and environmental-related applications thank to the high ratio of surface-to-volume and unprecedented electronic and optical characteristics (Ong et al, 2014b;Bai et al, 2015;Liang et al, 2015d;Fang et al, 2016;Kalantar-zadeh et al, 2016;She et al, 2017;Xueting et al, 2017). Among a large array of photocatalysts, research targeting at graphitic carbon nitride (g-C3N4) has been flourishing in recent years.…”
Section: Institute Of Materials Research and Engineering (Imre) Agenmentioning
confidence: 99%
“…By harvesting solar energy as the source of renewable energy, photocatalysis will make significant impacts in the areas of (1) light-driven water splitting to hydrogen (H2) and oxygen (O2) (Chen et al, 2010;Bai et al, 2016;Wei et al, 2016;Putri et al, 2017;Yubin et al, 2017), (2) conversion of carbon dioxide (CO2) to energy bearing fuels (Ong et al, , 2014cTan et al, 2014Tan et al, , 2016Tan et al, , 2017Gui et al, 2015;Guo et al, 2016a;Zhang et al, 2016c), (3) mineralization of waste and pollutants (Ong et al, 2014d,e;Fang et al, 2016;Liu et al, 2016c;Topcu et al, 2016;Zhao et al, 2016b), (4) selective organic transformations (Liu et al, 2014;Zhao et al, 2016a), and (5) disinfection of bacteria (Keane et al, 2014;Bing et al, 2015) (Figure 1). Very recently, two-dimensional (2D) semiconductor photocatalysts have triggered a renaissance of interest in the field of energy, and environmental-related applications thank to the high ratio of surface-to-volume and unprecedented electronic and optical characteristics (Ong et al, 2014b;Bai et al, 2015;Liang et al, 2015d;Fang et al, 2016;Kalantar-zadeh et al, 2016;She et al, 2017;Xueting et al, 2017). Among a large array of photocatalysts, research targeting at graphitic carbon nitride (g-C3N4) has been flourishing in recent years.…”
Section: Institute Of Materials Research and Engineering (Imre) Agenmentioning
confidence: 99%
“…Shape controlled materials, especially two-dimensional (2D) layered materials, including graphene, graphitic carbon nitride, graphene oxide, , layered metal oxide, , metal–organic frameworks, black phosphorus, and so on, are considered as appealing materials for catalysis, energy storage, flexible printing devices, and pollutant degradation. Because these materials with 2D morphology provide high specific surface area, a huge fraction of uncoordinated surface atoms, and more active surface sites for superior performances …”
Section: Introductionmentioning
confidence: 99%
“…23,24 Numerous studies have indicated that the electron-transport and -accepting properties of CQDs may be advantageous to guide the ow of photogenerated charges; therefore, signicant photocatalytic properties may be obtained by means of the construction of semiconductor/ carbon composites. 25,26 CQDs have been combined with hematite, BiOX (X ¼ Br or Cl), 27,28 32 and TiO 2 (ref. 33) for the photocatalytic oxidation (PCO) of organic pollutants in aqueous solutions.…”
Section: Introductionmentioning
confidence: 99%